Penilaian Berbasis Kelas dalam Meningkatkan Kualitas Pendidikan di RA Al-Hikmah Cintaratu - Halimatussa’diyah Halimatussa’diyah; Lulu Andiani; Nurafilah Febriyanti; Alfi Salma Fauziya; Ummu Laelatul Badriyah (Edu Happiness : Jurnal Ilmiah Perkembangan Anak Usia Dini, 2023)
This study aims to describe how class-based assessment improves the quality of education at RA Al-Hikmah. This research focuses on classroom-based assessment in improving the quality of education at RA Al-Hikmah. This research method is using a qualitative and descriptive approach. The results of the study show that the most effective way to improve the quality of education starts with teaching staff, students, and the role of parents who collaborate with schools as an effort to improve assessment. Class-based assessment will work if these factors support and strive to provide the best for the survival of the nation's children.